2019
DOI: 10.3747/co.26.4823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity, Dyslipidemia, and Diabetes on Trastuzumab-related Cardiotoxicity in Breast Cancer

Abstract: Background Clinical trials have demonstrated an increased risk of cardiotoxicity in patients with breast cancer (bca) receiving trastuzumab-based therapy. Diabetes, dyslipidemia, and obesity are known risk factors for cardiovascular disease. Studies have yielded conflicting results about whether those factors increase the risk of cardiotoxicity in patients with bca receiving trastuzumab.Methods In this retrospective cohort study, data were collected for 243 patients with bca positive for her2 (the human epider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 21 publications
1
19
1
1
Order By: Relevance
“…Since TIC patients often had more than one risk factor for cardiovascular disease and the number of TIC patients were only six we cannot define which of the identified risk factors that were correlated with development of TIC, since the power to do a multinominal logistic regression analysis was too low. However, our findings are in line with previous studies showing that TIC more often develops in older women with cardiovascular risk factors [6,23]. Furthermore, women in the TIC group had a lower LVEF than women in the control group at baseline indicating that women with lower LVEF may be at risk for developing TIC.…”
Section: Discussionsupporting
confidence: 92%
“…Since TIC patients often had more than one risk factor for cardiovascular disease and the number of TIC patients were only six we cannot define which of the identified risk factors that were correlated with development of TIC, since the power to do a multinominal logistic regression analysis was too low. However, our findings are in line with previous studies showing that TIC more often develops in older women with cardiovascular risk factors [6,23]. Furthermore, women in the TIC group had a lower LVEF than women in the control group at baseline indicating that women with lower LVEF may be at risk for developing TIC.…”
Section: Discussionsupporting
confidence: 92%
“…Cardiovascular disease and cancer not only share common mechanisms such as chronic inflammation but also exhibit common risk factors [ 47 , 90 ]. Diabetes mellitus, obesity and hypercholesterolaemia are not only considered to be risk factors for breast cancer but also are associated with increased cardiovascular side effects [ 67 , 101 ]. Although the reduced cardiotoxicity observed in a retrospective study of breast cancer patients treated with statins needs to be confirmed in prospective studies [ 17 ], we consider the treatment of hypercholesterolaemia to be useful.…”
Section: Cardiovascular Risk Factors and Diseases—risk Assessment Primentioning
confidence: 99%
“…Recent data suggest that diabetic risk reduction among cancer survivors was much lower compared to their non-cancer counterparts[ 17 ]. Uncontrolled diabetes, obesity, and hyperlipidemia have been shown to induce myocardial fibrosis which subsequently increases the incidence of symptomatic cancer treatment-related cardiotoxicity[ 18 ]. Hence, increased vigilance and multi-disciplinary collaborations between expert diabetic educator, a nutritionist and/or dietician, and primary care physicians are required for optimal diabetes management and maintaining the HbA1c goal of < 7% in most patients.…”
Section: Cardiovascular Risk Managementmentioning
confidence: 99%